PENGARUH KEPEMILIKAN INSTITUSIONAL, CAPITAL ADEQUACY RATIO (CAR) DAN LOAN DEPOSIT RATIO (LDR) TERHADAP PROFITABILITAS PADA BEBERAPA BANK YANG TERCATAT DI BURSA EFEK INDONESIA - Rika Kurniawati; Syamsu Alam; Mursalim Nohong (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
This study aims to determine the effect of institutional ownership, capital adequacy ratio (CAR), loan deposit ratio (LDR) to profitability at several banks listed on the Indonesia Stock Exchange. This research uses descriptive analysis with quantitative approach and using multiple linear regression analysis technique assisted with SPSS program version 24. Quantitative approach is used to find accurate information and data and identify problems or to get justification of circumstances and activities that are being walk. The results showed that institutional ownership had a positive and significant impact on profitability, capital adequacy ratio (CAR) has a positive and significant impact on profitability, and loan deposit ratio (LDR) has a positive and significant impact on profitability.